Chemical Modification of Poly(Vinyl Chloride) Resin to Improve the Photostability Processes - Kamil, Adel (Al-Nahrain Journal of Science, 2018)
The photostability of PVC films phenylphrine HCl acid complexes was investigated. PVC reacts with phenyl phrine HCl acid (L) in THF to prepare PVC-L compound, which characterized by various spectroscopic methods. PVC-L has been reacted with different metal ions to form PVC-L-MII complexes. The structures of these complexes were characterized by IR and Uv-Vis. Spectrophotometry. The photostabilization activity of these compounds was determined by monitoring different indices with irradiation time. The changes in viscosity average molecular weight of PVC with irradiation time were also confirmed (using THF as a solvent). The quantum yield of the chain scission (Φcs) of modified polymer ﬁlms was evaluated and found to range between 4.990x103 and 1.147x104. Surface morphology of the films was studied by atomic force microscope (AFM). All results show that the rate of photodegradation of PVC-L-MII films following the trends: PVC‐L‐CdII > PVC‐L‐ZnII > PVC‐L-CuII > PVC‐L-CoII > PVC‐L > PVC. According to the experimental results obtained several mechanisms were indicated depending on the structure of the PVC-L-MII complexes.